As invisíveis do cárcere: interfaces identitárias de mulheres aprisionadas - Almeida, Giseliane Medeiros (2018)
This research aims to describe and analyze the process of historical construction of subjectivities of women prisoners of Paulo Afonso’s Penal Set, highlighting the diversity of experience and invisibility of the condition of the female public relatively to male prison public. The epistemological assumptions of qualitative-interpretative methodology of post-critical inspiration, stands as theoretical north for comprehension of general categories of knowings production (knowledge, truth, power relations and speeches) concerning to gender, education and crime. The review of the literature concerning the female crime relatively to male crime disclose the exiguity of studies and researches about the theme, particularly in educational scope. It were consulted several informational sources and instruments of data collection, such as: participative observation, record at field diary, and semi-structured interviews conducted with 15 women and 10 men, giving special highlight to women voices, the cultural construction of identities and ways of subjectivation. Discursive textual analyze reveals dimensions of gender relations, disadvantageous experiences of forged intimacy, cloistered by power relations, iron grids and walls in jail. The life’s histories uncover episodes of violence, passion, fear, pain and suffering in daily life. The prison system intercalates gender and education into the educative processes in a wide, diversified sense, encompassing the several formal and informal ambit, institutional and non-institutional. On the other hand, both educative scenarios reflect the binary conception about gender (class, race, age/generation, sexual orientation) stating standards and ways of being and living as a woman or a man in society. The results question the guidelines, aiming the humanization of the service conditions, guarantee of rights and dignity, free legal aid, qualifications opportunities, so the prisoners may glimpse a future without discrimination. It is worth emphasizing that, instead of closing parentheses and present closed conclusions, we point the sensation of having touched and hit the center and object of this research, which concerns to the female prisoners.